DIGITAL TOOLS AND LEARNER AUTONOMY IN ENGLISH LANGUAGE LEARNING - Turaxanova Lobar Ikram qizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract:      This study explores the role of digital tools in enhancing learner autonomy in English language learning contexts. In the era of digital transformation, learners increasingly rely on mobile applications, online platforms, and artificial intelligence-based tools to manage their own learning process. The purpose of this research is to investigate how digital tools influence students’ independence, motivation, and responsibility in learning English. A mixed-method approach was used, combining survey data and semi-structured interviews with English language learners. The findings indicate that digital tools significantly contribute to learner autonomy by providing flexible access to resources, personalized learning paths, and opportunities for self-assessment. However, challenges such as lack of guidance and digital distractions were also identified. The study concludes that digital tools are powerful facilitators of autonomous learning when properly integrated into language education.